FORMULASI GEL EKSTRAK LENGKUAS (Alpinia galanga L.) SEBAGAI ANTIJAMUR DENGAN BASIS HIDROKSI PROPIL METIL SELULOSA (HPMC) DAN CARBOPOL - Wintari Taurina; Mohamad Andrie (Faculty of Pharmacy, Universitas Gadjah Mada, 2013)
Infection of Malassezia furfur on skin can be caused by bad factor. One of the materials that can be used as an antifungal is Lengkuas rhizome extract (Alpinia galanga L.). This study had purpose to determine the antifungal activity and the effectiveness of gels Lengkuas rhizome extract on pathogenic fungi using maseration method with etanol 96%. Gel making is used HPMC and carbopol base. Testing activity of extract and testing the effectiveness of the gel by disc diffusion method (Kirby-Bauer test). Screening result showed that the extract contains triterpenoids, flavonoids and essential oil. Based on the test results against Malassezia furfur, antifungal activity of the extract in the gel increased compared to extracts without formulated into a gel. But the activity increasing was not significant based on statistical analysis with one-way ANOVA test obtained a significance of 0.234 (p> 0.05).